Sustaining platforms as commons: perspectives on participation, infrastructure, and governance. Issue 3 (3rd July 2019) - Poderi, Giacomo
ABSTRACT: This work finds its place within Participatory Design (PD) as a specific approach to co-design that focuses on the politics of technological innovation and socio-technical transformations. In particular, the article contributes to the repositioning of co-design in the age of platform capitalism by engaging with the question: how can participatory designers approach interventions for the long-term sustainability of platforms as commons? As the contradictions and limitations of platform capitalism become increasingly evident, to engage with such a challenge is a way to pursue PD's renewed political agenda. The article foregrounds the concept of platforms as commons to bring designers' attention towards those platform arrangements which are antithetical to platform capitalism exploitative ones. By building on Free and Open Source Software (FOSS), as a paradigmatic case of platform as commons, the article outlines participation, infrastructure, and governance as relevant perspectives for framing broad areas of sustainability concerns; and it articulates them along four approaches for supporting long-term sustainability in practice: maintaining, scaling, replicating, and evolving. Ultimately, this article provides participatory designers with a map of possible orientations to frame and support their work, research or interventions around the long-term sustainability of platforms as commons.